Controller Design for Position Tracking of Nonlinear System - Md Rozali, Sahazati; Kamarudin, Muhammad Nizam; Rahmat, Mohd Fua'ad; Husain, Abdul Rashid; Zainal Abidin, Amar Faiz (IEEE, 2013)
Usually, the nonlinearities existing in the system is eliminated by using linearization method. However, backstepping method allows additional nonlinearities to be created and introduced to the control process so that the undesirable nonlinearities can be cancelled out from the system. In this work,position tracking of electrohydraulic actuator system is taken as a numerical example since it is highly nonlinear. Backstepping controller is designed for the system without disturbance and with additional disturbance is given to its actuator. Control parameter of the designed controller for both condition is then optimized by using Particle Swarm Optimization method. The performance of the designed controller to the system is observed through its tracking error.